Be connected, exchange, but also create: teachers' professional growth within an online community of practice - Elena Gabbi (Firenze University Press, 2023)
This paper aims to explore the link between participation in the eTwinning online community of practice and the possible impact on the professional development of teachers who sign up, by investigating the processes and dynamics perceived through the voices of the most experienced participants. Following the theoretical framework of the value of the online community for teachers' professional development and the description of the digital and organisational system resources, the methodology of the qualitative study and the results of the thematic analysis conducted are described. By a focus group conducted with 15 users, the study defined a sequence of progressive steps in network participation linked to learning dynamics peculiar to each of the three phases of access to the system, exploration of community resources and practices, and active experimentation with the available resources.   Essere collegati, scambiare, ma anche creare: la crescita professionale degli insegnanti all'interno di una comunità di pratica online. Il presente lavoro mira ad indagare il nesso tra partecipazione alla comunità online di pratica di eTwinning e le eventuali ricadute sullo sviluppo professionale degli insegnanti che si iscrivono, attraverso un affondo nei processi e nelle dinamiche percepite attraverso la voce dei partecipanti più esperti. In seguito all'inquadramento teorico della valenza della comunità online per la crescita professionale dei docenti e della descrizione delle risorse del sistema digitale e organizzativo, viene descritta la metodologia dello studio qualitativo e i risultati dell'analisi tematica condotta. Tramite un focus group condotto con 15 utenti, lo studio ha definito una sequenza di passaggi progressivi nella partecipazione alla rete collegati a dinamiche di apprendimento peculiari di ciascuna delle tre fasi di accesso al sistema, esplorazione delle risorse e delle pratiche della comunità e sperimentazione attiva delle risorse disponibili.